Preparation and characterization of novel hybrid of chitosan-g-lactic acid and montmorillonite - Depan, Dilip; Kumar, Annamalai Pratheep; Singh, Raj Pal (Journal of Biomedical Materials Research Part A, 2006)
The utilization of biopolymers and the development of organic-inorganic hybrids are ever increasing interest of material science researchers around the globe for various applications. The present attempt is intended to prepare nanocomposites of lactic acid grafted chitosan and layered silicates. Nanocomposites were prepared by dissolving chitosan and dispersing sodium montmorillonite in aqueous solution of L-lactic acid with subsequent heating and film casting. They were characterized by conventional techniques such as Fourier transform infrared spectroscopy, X-ray diffractometry, thermogravimetric analysis, energy dispersive X-ray spectroscopy, and elemental analysis. The results from polar optical and transmission electron microscopic measurements are also discussed. Sorption behavior of samples has been followed by measuring swelling degree and contact angle. The films have shown enhanced hydrophilicity when compared with polylactic acid (PLA). Issues on the interactions of polycationic chitosan with clay are also discussed. It is observed that nanocomposites are exhibiting better thermal and physical properties than neat chitosang-LA and PLA. (c) 2006 Wiley Periodicals, Inc.
Keywords: Chitosan; contact angle; graft copolymerization; Nanocomposites; polylactic acid; water absorption

Novel hybrid of clay, cellulose, and thermoplastics. I. preparation and characterization of composites of ethylene-propylene copolymer - Kumar, Annamalai Pratheep; Singh, Raj Pal (Journal of Applied Polymer Science, 2007)
{The present study is aimed to prepare hybrid materials by incorporating layered silicates and microcrystalline cellulose into thermoplastic polymer. Using ethylene-propylene (EP) copolymer as thermoplastic polymer matrix and maleated EP (MEP) copolymer as compatibilizer, three types of composites were prepared by (i) melt mixing of cellulose with thermoplastics [
Keywords: abrupt contraction; Arbitrary Lagrangian Eulerian; finite element; simulations

Photo-stabilization of EPDM-clay nanocomposites: effect of antioxidant on the preparation and durability - Lonkar, Sunil P.; Kumar, A. Pratheep; Singh, Raj Pal (Polymers for Advanced Technologies, 2007)
The present study is to examine the photo-stabilization effect of an antioxidant on the photo-oxidation of ethylene-propylene-diene monomer (EPDM)-clay nanocomposites. During the preparation of EPDM-clay nanocomposites via melt processing antioxidants are usually incorporated along with clay, which allows phenolic antioxidant molecules to get adsorbed onto acidic clay platelets and their interaction with metallic impurities reduces the stabilizing efficiency of the antioxidant. The nanocomposites were obtained by solution dispersion followed by melt compounding of EPDM and organophilic montmorillonite (OMMT). The samples were characterized by conventional tools such as X-ray diffraction (XRD), Fourier Transform Infra Red (FT-IR) spectroscopy, and thermo-gravimetric analysis (TGA). It was found, upon photo-irradiation (lambda > 290 nm) studies by following the changes in functional groups and surface morphology, that photo-degradation was lowered by the antioxidant and the efficiency of the antioxidant could be improved by initial incorporation of antioxidant in the EPDM matrix. In EPDM-clay nanocomposites, a stabilizing activity of the antioxidant was observed above some threshold concentration of the antioxidant. The relationship between the nanoclay reinforcement and stabilizing efficiency in terms of photo-oxidation and surface morphology for their applicability are discussed. The methodology adopted for this study is also justified through our observation. Copyright (C) 2007 John Wiley & Sons, Ltd.
International Conference on Frontier in Polymer Science and Technology, Calcutta, INDIA, FEB 10-12, 2006
Keywords: ethylene-propylene-diene monomer; nanocomposites photo-degradation antioxidant and stabilization

Synthesis, characterization, and performance evaluation of polymeric hindered amine light stabilizers (HALS) in EPDM - Rana, Sravendra; Singh, Raj Pal (E-Polymers, 2007)
Polymeric hindered amine light stabilizer (HALS), wherein the hindered amine functionality was attached to the brominated ethylene-propylene-diene terpolymer (EPDM) was synthesized. The brominated EPDM was synthesized as an intermediate for the synthesis of a new polymeric hindered amine light stabilizer. The grafting and functionalization reactions were characterized by FTIR and (HNMR)-H-1 spectroscopy. The photostabilizing efficiency of this polymeric HALS was studied and compared with conventional HALS under accelerated weathering conditions. The results of the study give evidence for superiority of polymeric HALS over that of melt blended conventional HALS.
Keywords: EPDM; Photostabilization; polymeric HALS

Biocomposites of cellulose reinforced starch: improvement of properties by photo-induced crosslinking - Kumar, Annamalai Pratheep; Singh, Raj Pal (Bioresource Technology, 2008)
In the present study, the composite films have been prepared from the aqueous dispersions of starch with microcrystalline cellulose using glycerol as plasticizer and irradiated under ultraviolet (UV) light using sodium benzoate as photo-sensitizer. Photocrosslinking was characterized by measuring the water absorption under 100% relative humidity, swelling degree and gel fraction in dimethylsulphoxide (DMSC), upon irradiation time. Both, the incorporation of cellulose and photo-irradiation were found to decrease the water absorption, swelling in DMSO and increase the gel fraction. Thermal transitions indicated the anti-plasticization of amylopectin chains at the fiber/matrix interface. With increasing content of cellulose and photo-irradiation time, the tensile modulus and strength were found to improve. It is summarized that the combination of cellulose reinforcement and photo-crosslinking of matrix has improved the physical and mechanical properties. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Biocomposites; cellulose; Photo-irradiation and crosslinking; Starch

Cationic polymerization of epoxides using novel xanthenyl phosphonium salts as thermo-latent initiator - Gupta, Mukesh Kumar; Singh, Raj Pal (Polymer Bulletin, 2008)
The present article describes the effect of steric and electronic factors on the efficiency of initiators based on novel xanthenyl phosphonium salts for cationic polymerization of epoxide monomers. 2-substituted (I(H), I(Cl), I(Me), and I(OMe)) xanthenyl phosphonium hexafluoroantimonate were synthesized and characterized by NMR ((1)H, (13)C and (31)P) and IR spectroscopy. The order of initiator activity in polymerization of glycidyl phenyl ether (GPE), was found as I(H)> I(Cl)> I(Me)> I(OMe). To understand the effect of steric factor, the polymerization of cyclohexene oxide (CHO) was performed and the order of activity was found as I(Cl)> I(H)> I(Me) > I(OMe). All the initiators were found to be latent at ambient temperature and initiates polymerization on thermal initiation. The order of initiator activity was influenced by electronic and steric factors in the system. The thermal stability of these salts was measured by Thermo gravimetric analysis (TGA). The solubility of the initiators in various organic solvents and epoxy monomers is also discussed.

Durability of crosslinked polydimethylsyloxanes: the case of composite insulators - Delor-Jestin, Florence; Tomer, Namrata S.; Singh, Raj Pal; Lacoste, Jacques (Science and Technology of Advanced Materials, 2008)
Most applications of silicones are linked to their hydrophobic properties and (or) their high resistance to ageing (e. g. thermal ageing and photoageing). However, when placed in extreme environments, these materials can fail as in the case of epoxy/fiber glass composite powerlines insulators, where crosslinked polymethylsyloxanes (PDMSs) are used as the protective envelope (housing) of the insulator. We report on the behavior of both pure/noncrosslinked PDMSs and typical formulations used in industrial insulators, i.e. containing peroxide crosslinked PDMS, alumina trioxide hydrated (ATH) and silica. Special attention is paid on both (i) the sources of potential degradation and (ii) the best analytical methods that can be applied to the study of very complex formulations. (i) Aside from conventional types of ageing such as photo-ageing and thermal, hydrolytic, and service life ageings, treatments with acidic vapors, plasma and ozone possibly generating species from the reaction of a high electric field with air were also performed, which allowed to accelerate electrical and out-door ageings and to obtain differently aged materials. (ii) Aside from conventional analytical methods of polymer degradation such as FTIR/ATR spectroscopy and SEC, TG, hardness measurements, more specific methods like photo/DSC, TG/IR, thermoporosimetry, resistivity and density measurements were also performed to characterize the chemical and physical evolutions of polymer materials. In particular, it was found that treatment with nitric acid vapor has detrimental effects on the properties of both fire retardants (e. g. ATH) and PDMSs, affecting the hardness and resistivity of the formulated material.
International Conference on Magneto-Science, Hiroshima, JAPAN, NOV, 2007
Keywords: composite insulators; durability; PDMS; post-crosslinking; silicone

Preparation and characterization of novel hybrid of chitosan-g-PDMS and sodium montmorrilonite - Depan, Dilip; Kumar, Bijandra; Singh, Raj Pal (Journal of Biomedical Materials Research Part B-Applied Biomaterials, 2008)
Preparation and properties of Chitosan (CS)-clay nanocomposites grafted with polydimethyl siloxane (PDMS) with different clay ratios are herein discussed. CS is intercalated into sodium montmorrilonite and PDMS is grafted onto CS under UV irradiation. Sample films of CS intercalated into clay and grafted with PDMS were prepared by solvent casting method with varying amount of nanoclay and PDMS. They were characterized by conventional techniques such as X-ray diffractometry, fourier transform infrared spectroscopy, C-13 NMR, thermo gravimetric analysis, and differential thermal analysis. Sorption behavior of samples has been followed by measuring swelling degree and issues on the interactions of biopolymers with clay are also discussed. The water absorption of composites films reduces with an increase in the amount of incorporated clay. This is due to the barrier formation in the form of cross-linking points, which prevents water permeation into CS. The amount of adsorbed water is more, when the amount of CS exceeds the amount of PDMS. This shows high water retention capacity of CS. (c) 2007 Wiley Periodicals, Inc.
Keywords: Chitosan; graft copolymerization; Nanocomposites; PDMS; water absorption

Cell proliferation and controlled drug release studies of nanohybrids based on chitosan-g-lactic acid and montmorillonite - Depan, Dilip; Kumar, Annamalai Pratheep; Singh, Raj Pal (Acta Biomaterialia, 2009)
The present paper reveals the potential uses of novel hybrids of chitosan-g-lactic acid and sodium montmorillonite (MMT) in controlled drug delivery and tissue engineering applications. The drug-loaded novel nanohybrid films and porous scaffolds have been prepared by solvent casting and freeze-drying of the grafted polymer solution, respectively. Sodium Ibuprofen was loaded into nanohybrids of chitosan-g-lactic acid/sodium montmorillonite (CS-g-LA/MMT). Grafting of lactic acid and the drug loading were characterized by Fourier transform infrared spectroscopy. Formation of intercalated nanocomposites was confirmed by X-ray diffraction. Mechanical properties measurements have shown improvement in modulus and strength with expense of elongation by MMT reinforcement. The nanohybrids were found to be stable regardless of pH of the medium. The cell proliferation profile also shows that prepared nanohybrids are biocompatible. MMT reinforcement was found to control the drug (Ibuprofen) release rate in phosphate buffer saline solution (pH 7.4). MMT clay is therefore a viable additive for formulating sustained drug delivery systems based on lactic acid grafted chitosan. (C) 2008 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Chitosan; clay; Controlled release; drug delivery systems; Nanocomposites

Nanoscale particles for polymer degradation and stabilization-trends and future perspectives - Kumar, Annamalai Pratheep; Depan, Dilip; Tomer, Namrata Singh; Singh, Raj Pal (Progress in Polymer Science, 2009)
The field of nanoscience and nanotechnology is extending the applications of physics, chemistry, biology, engineering and technology into previously unapproached infinitesimal length scales. The polymer-nanoparticles/nanocomposites have been the exponentially growing field of research for developing the materials in last few decades and have been mainly focusing on the structure-property relationships and their development. Since the polymer-nanocomposites have been the staple of modern polymer industry, their durability under various environmental conditions and degradability after their service life are also essential fields of research. Thus, this article is intended to review the status of worldwide research in this aspect. Among various nanoparticulates, clay minerals and carbon nanotubes are more often used in enhancing physical, mechanical and thermal properties of polymers. In very few systems, the nano particulates have been incorporated into polymer as `nano-additives' for both purposes: degradation and stabilization of polymers. The degradation and durability of polymers is reviewed in the presence of nanoparticles/nanocomposites under different environmental conditions. Nanoparticle-induced biodegradation of polymers is also discussed. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Carbon nanotubes; clay; Degradation and stabilization; Nanocomposites; Nanoparticles; Polymer

Novel allylic phosphonium salts in free radical accelerated cationic polymerization - Gupta, Mukesh Kumar; Singh, Raj Pal (Polymer Bulletin, 2009)
In the present study, the synthesis and evaluation of novel allylic phosphonium salts as addition fragmentation agents in combination of conventional (photo-/thermal) free radical source for cationic polymerization are described. The amide based allylic phosphonium salts, namely 2-(N, N-dimethylcaboxy-propenyl) triphenylphosphonium hexafluoroantimonate (DMTPH) and 2-(morpholinocarboxy-propenyl) triphenyl phosphonium hexafluoroantimonate (MTPH) were synthesized and characterized. The thermal and photo-latency of these salts was examined with and without free radical sources in bulk polymerization of cyclohexene oxide (CHO) salts at 70 A degrees C and lambda > 290 nm irradiation, respectively. In presence of thermal free radical source, the order of activity was observed as PAT > BPO > AIBN. The order of activity of free radical sources on photopolymerization was found to be benzoin > benzophenone > TMDPO. In addition, photopolymerization of other cationically polymerizable monomers (such as n-butyl vinyl ether, isobutyl vinyl ether, N-vinyl carbazole and glycidyl phenyl ether) was also examined at lambda > 290 nm irradiation. It is concluded that the rate of cationic polymerization can be accelerated using novel phosphonium salts with combination of free radical sources, by both thermal and photochemical mode.
Keywords: Addition fragmentation agent; Cationic polymerization; Initiator; phosphonium salt; Photopolymerization

Novel dibenzocycloheptenyl phosphonium salts as thermolatent initiator in cationic polymerization - Gupta, Mukesh Kumar; Singh, Raj Pal (Journal of Applied Polymer Science, 2009)
In this study, novel thermolatent cationic initiators based on dibenzocycloheptenyl phosphonium salts (1a, 1b, 1c, 1d, 2a, and 3a) were synthesized and their efficiency was examined in bulk polymerization of glycidyl phenyl ether (GPE). The polymerization of GPE was performed with 1 mol % of dibenzocycloheptenyl triphenylphosphonium salts (1a-1d) with different counter anions (SbF(6)(-), PF(6)(-), AsF(6)(-), and BF(4)(-)) at 25-200 degrees C for 1 h. The order of initiator activity was found as 1a > 1d > 1b > 1c. To examine the effect of phosphine moiety, the activity of la was compared with dibenzocycloheptenyl-tri-n-butylphosphonium hexafluoroantimonate (2a). The order of initiator activity was observed as 1a > 2a. The initiator activity of la was compared with that of 10,11-dihydro-dibenzocycloheptenyltriphenylphosphonium hexafluoroantimonate (3a) to understand the effect of extended conjugation in dibenzocycloheptenyl ring. In general, with the increase in the polymerization temperature, conversion (%) also increases. The solubility of initiators in various solvents and epoxy monomers was also examined. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 112: 3707-3713, 2009
Keywords: Cationic polymerization; glycidyl phenyl ether; initiators; phosphonium salt; thermolatent

Thermally induced cationic polymerization of glycidyl phenyl ether using novel xanthenyl phosphonium salts - Gupta, Mukesh Kumar; Singh, Raj Pal (Macromolecular Research, 2009)
The present study firstly describes the synthesis of novel, thermo-latent initiators based on xanthenyl phosphonium salts with different counter anions and phosphine moieties and secondly examines their efficiency in the bulk polymerization of glycidyl phenyl ether (GPE). The polymerization was performed with phosphonium salt initiators (I(SbF6), I(PF6), I(AsF6) and I(BF4)) at ambient temperature to 200 degrees C for 1 h. The order of initiator activity was I(SbF6) > I(PF6) > I(AsF6) > I(BF4). To examine the effect of the phosphine moiety on the initiator activity, polymerization was carried out with I(SbF6) (Ph(3)P) and II(SbF6) (Bu(3)P) at ambient temperature to 170 degrees C for 1 h. The order of reactivity was I(SbF6) > II(SbF6). In general, the conversion percentage increased with increasing polymerization temperature. The thermal stability of these salts was measured by then-no gravimetric analysis (TGA). The solubility of phosphonium salts in various organic solvents and epoxy monomers was also investigated.
Keywords: Cationic polymerization; glycidyl phenyl ether; phosphonium salts; thermo-latent

Enhancement of thermal stability and phase relaxation behavior of chitosan dissolved in aqueous l-lactic acid: using `silver nanoparticles' as nano filler - Rana, V. K.; Pandey, Asutosh K.; Singh, Raj Pal; Kumar, B.; Mishra, Satyendra; Ha, Chang-Sik (Macromolecular Research, 2010)
Chitosan films with various compositions of silver nanoparticles were prepared by solution casting with an aqueous solution of chitosan and l-lactic acid. The chitosan/Ag nanocomposites were characterized by wide angle Xray diffraction (WAXD) and UV-vis spectroscopy. An analysis of the surface topography and size of the Ag nanoparticles (<= 100 nm) were characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM), respectively. Thermogravimetric analysis (TGA/DTA) confirmed the increase in thermal stability with increasing Ag nanoparticle content in the nanocomposites. Dynamic thermal analysis (DMA) was used to examine the phase relaxation behavior of chitosan and its nanocomposites. The conductivity of chitosan/Ag nanocomposites was considered with respect to the frequency. Contact angle measurements were used to characterize the surface twistability, surface cleanliness, and hydrophilic/hydrophobic nature of the surface.
Keywords: Chitosan; conductivity; contact angle; relaxation; silver nanoparticles

Novel addition-fragmentation agent in cationic photopolymerization - Gupta, Mukesh Kumar; Mehare, Rupali S.; Singh, Raj Pal (Polymer Bulletin, 2010)
The aim of present study is to examine the photo-initiation efficiency of N,N-dimethylacrylamide-based allylic ammonium salt as one component addition-fragmentation agent (cationic photoinitiator cum radical source) in free radical accelerated cationic polymerization. Novel addition-fragmentation agent (AFA), 2-(N,N-dimethylcarboxy-3-propenyl)(phenylcarbonyl-4-phenylene) dimethyl ammonium hexafluoroantimonate (DMPDA) was synthesized as cationic photoinitiator and its initiation efficiency was examined in polymerization of cyclohexene oxide (CHO), isobutyl vinyl ether (IBVE), and n-butyl vinyl ether (n-BVE) in CH(2)Cl(2) solvent at wavelength lambda > 290 nm. The rate of polymerization increases with the increase in initiator concentration and reaction time. The results demonstrate that DMPDA acts as an efficient photoinitiator (AFA) without use of radical source in free radical accelerated cationic polymerization.
Keywords: Addition-fragmentation agent; Ammonium salt; Benzophenone; Cationic polymerization; Onium salt; Photopolymerization

Preparation and characterization of bioceramic nanocomposites based on hydroxyapatite (HA) and carboxymethyl cellulose (CMC) - Kumar, Annamalai Pratheep; Mohaideen, Kamal Khaja; Alariqi, Sameh A. S.; Singh, Raj Pal (Macromolecular Research, 2010)
We report the synthesis of biomimetic nanocomposites based on carboxymethyl cellulose (CMC) and hydroxyapatite (HA) nanoparticles via a co-precipitation method. Physico-chemical characterization was performed before and after calcination by Fourier transform infrared (FTIR) spectroscopy, solid state (31)P nuclear magnetic resonance (NMR) spectroscopy, and thermogravimetric analysis (TGA). The formation of nanocomposites was observed by wide angle X-ray diffraction (WAXD), scanning electron microscopy (SEM) with energy dispersive X-ray analysis (EDX), and transmission electron microscopy (TEM). The spectral and crystallographic data indicated the formation of hydroxyapatite in the presence of CMC. They were observed as aggregates of HA nanoparticles and CMC, whose sizes were approximately similar to 260 +/- 40 nm. The crystallite size of the hydroxyapatite particles decreased (with 2 wt% 18 +/- 3 nm) with increasing CMC content. The morphological aspects of the calcined samples revealed the sintering ability of HA nanoparticles. Nanocomposites of hydroxyapatite nanoparticles that mimic the process of nucleation and growth in nature can be prepared using biomacromolecules such as CMC.
Keywords: biopolymer; cellulose; hydroxyapatite; Nanoparticles; Particle size; X-ray diffraction

Preparation and characterization of novel hybrid of bio-assisted mineralized Zn-Al layered double hydroxides using chitosan as a template - Depan, Dilip; Singh, Raj Pal (Journal of Applied Polymer Science, 2010)
The purpose of this study was to prepare and characterize a novel nanohybrid prepared from the template-assisted mineralization of Zn-Al Layered Double Hydroxide (LDH) onto the surface of Chitosan (CSI), with an emphasis on morphology, biocompatibitity, and its use as an efficient drug carrier agent. The as prepared LDH is highly crystalline, with platelet-like morphology and curved tactoids when nucleated onto the surface of CSI. Our results indicate that the -OH and -NH functional moieties on CSI can direct an ordered structure of LDH, due to the electrostatic interaction between biopolymer and inorganic lamellae. We have been successful to intercalate an anti-inflammatory drug, Sodium Ibuprofen (Ibu), into LDH, through conventional coprecipitation method. LDHs are endowed with great potential for delivery vector because their stacked layers lead to safe reservation of biofunctional molecules or genes, and their ion exchangeability and solubility in acidic media (pH < 4) give rise to the controlled release of drug molecules. According to the cell-growth studies, LDHs are found as cell viable up to the concentration of 500 mu g/mL. This study reveals that LDH not only plays a role of a biocompatible-delivery matrix but also facilitates a significant increase in the delivery efficiency. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 115:3636-3644,2010
Keywords: bio-assisted mineralization; cell-growth studies; Chitosan; drug delivery systems; layered double hydroxides

Ultrasound-triggered release of ibuprofen from a chitosan-mesoporous silica composite - a novel approach for controlled drug release - Depan, Dilip; Saikia, Lakshi; Singh, Raj Pal (Macromolecular Symposia, 2010)
In this work, an attempt was made to synthesize a novel Chitosan-Mesoporous silica (CS-MS) hybrid composite to design a drug delivery system based on ultrasound triggered stimuli-responsive smart release. The in-vitro drug release properties of both the Mesoporous Silica (MS) and Chitosan (CS) hybrids were investigated. Ibuprofen (Ibu) was used as a model drug. The results from powder X-Ray diffraction (XRD) patterns, and BET N(2) adsorption isotherms exhibited that MS can accommodate drug molecules into the lumen of the channels and pores. Drug release, stimulated by temperature and pH of the release media was also investigated. We studied the Ultrasound (US) triggered release of Ibu in a simulated body fluid (pH 7.4). The results exhibited that US can be used as a non-invasive technique for drug release from polymeric materials. The enhancing effect of ultrasound on drug release is due to the Cavitation effect, without causing any significant destruction on the polymer morphology.
4th International Symposium on Macro-and Supramolecular Architectures and Materials, Dusseldorf, GERMANY, SEP 07-11, 2008
Keywords: Chitosan; drug delivery systems; ibuprofen; Mesoporous silica; Ultrasound

Hierarchical mesoporous bio-polymer/silica composites co-templated by trimethyl chitosan and a surfactant for controlled drug delivery - Rana, Vijay Kumar; Park, Sung Soo; Parambadath, Surendran; Kim, Mi Ju; Kim, Sun-Hee; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Medchemcomm, 2011)
In this communication, we report the facile synthesis of hierarchical mesoporous bio-polymer/silica composite materials with bimodal mesopores using a dual-template of the cationic N,N,N-trimethyl chitosan (TMCs) and the anionic sodium dodecyl sulfate (SDS) via one-step synthetic strategy. Tetraethoxysilane (TEOS) was used as a silica source. The nitrogen adsorption/desorption measurements and transmission electron microscopy analysis showed the hierarchical structure of the mesoporous bio-polymer/silica composites with bimodal mesopores having an average pore size of 5-7 nm with the visible voids between the silica nanoparticles, which allow the mesoporous bio-polymer/silica composites to encapsulate a large number of guest drug molecules, Ibuprofen (IBU) or 5-fluorouracil (5-FU), due to their high surface area and pore volume. In addition, the mesoporous chitosan-silica composites also had a long term biocompatibility for the target release of the drug molecules to the CEM cells, MCF cells, etc. as well as a pH sensitive controlled release behavior of the drug molecules.

Influence of reactive compatibilization on the structure and properties of PP/LDH nanocomposites - Lonkar, Sunil P.; Therias, Sandrine; Leroux, Fabrice; Gardette, Jean Luc; Singh, Raj Pal (Polymer International, 2011)
Polypropylene (PP)/layered double hydroxide (LDH) nanocomposites were prepared by the direct melt intercalation method usingmaleic anhydride grafted polypropylene (PP-g-MAH) as a reactive compatibilizer. The compatibilization effects provided by PP-g-MAH in different weight fractions and their influence on the structure and properties of the final nanocomposites were investigated. The interactions and structural morphology of the nanocomposites were examined by Fourier transform infrared spectroscopy, X-ray diffraction and transmission electronmicroscopy. Thermal, mechanical and rheological properties of these nanocomposites were investigated as a function of compatibilizer concentration. The detailed morphological and X-ray diffraction results revealed that the degree of LDH dispersion increases as the amount of PP-g-MAH increases. Study of the linear viscoelastic properties showed that the storage modulus G' is very sensitive to the microstructure of the nanocomposite. The thermal properties of the nanocomposites were significantly influenced by the weight fraction of PP-g-MAH due to the shielding and nucleating effect of exfoliated layers. Both the tensile strength and modulus showed substantial improvements with increasing PP-g-MAH content, while the elongation at break substantially decreased, although the presence of PP-gMAH somewhat improves these values. The overall results showed that 10 wt% of compatibilizer is optimum to achieve nanocomposites with better performance. (C) 2011 Society of Chemical Industry
Keywords: compatibilization; layered double hydroxides; Nanocomposites; polypropylene; Rheology; thermomechanical properties

Synthesis and drug-delivery behavior of chitosan-functionalized graphene oxide hybrid nanosheets - Rana, Vijay Kumar; Choi, Myeon-Cheon; Kong, Jin-Yeon; Kim, Gwang Yeon; Kim, Mi Ju; Kim, Sun-Hee; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Macromolecular Materials and Engineering, 2011)
Chitosan-functionalized graphene oxides (FGOCs) were successfully synthesized. FGOCs were found to significantly improve the solubility of the GO in aqueous acidic media. The presence of organic groups was confirmed by means of XPS and TGA. Restoration of the sp(2) carbon network and exfoliation of graphene sheets were confirmed by Raman spectroscopy, UV-visible spectroscopy and WAXD. The SEM and AFM investigations of the resultant FGOCs showed that most of the graphene sheets were individual and few were layered. Controlled release behavior of Ibuprofen and 5-fluorouracil was then investigated. We found that FGOCs are a promising new material for biological and medical applications.
Keywords: Biocompatibility; Chitosan; drug delivery systems; functionalization of polymers; solution properties

Glycolic acid-g-chitosan-gold nanoflower nanocomposite scaffolds for drug delivery and tissue engineering - Kumari, Sangeeta; Singh, Raj Pal (International Journal of Biological Macromolecules, 2012)
This paper reports a simple novel method for the synthesis of flower like gold nanoparticle (three dimensional branched nanoparticle) with >30 tips, under controlled temperature condition. Formation of flower like Au nanoparticle was confirmed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Next step of this paper reveals the potential use of novel hybrids of chitosan-g-glycolic acid and gold nanoflower (AuNF) in controlled drug delivery and tissue engineering applications. The drug loaded novel nanohybrid scaffold is prepared by freeze drying of grafted polymer solution. Grafting of glycolic acid to the chitosan and incorporation of drug were evaluated by Fourier transform infrared spectroscopy (FTIR). The nanohybrid scaffolds were found to be stable towards the pH of the medium. The cell viability study shows that prepared nanohybrid scaffolds are biocompatible. Gold nanoflowers were found to control the drug release rate in the buffer solution (pH 7.4). Therefore, for the glycolic acid grafted chitosan based system, gold nanoflowers are the viable additive for drug delivery. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chitosan; Drug delivery system; Glycolic acid grafting; Gold nanoflower; Nanocomposite

Glycolic acid-g-chitosan-Pt-Fe3O4 nanoparticles nanohybrid scaffold for tissue engineering and drug delivery - Kumari, Sangeeta; Singh, Raj Pal (International Journal of Biological Macromolecules, 2012)
This work presents the potential use of novel nanohybrid based on chitosan-g-glycolic acid and Pt-Fe3O4 composite nanoparticles in drug delivery and tissue engineering applications. The Pt-Fe3O4 hybrid nanoparticles are prepared by thermal decomposition of H2PtCl6 center dot 6H(2)O at high temperature. The prepared nanoparticles were characterized by transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and physical property measurement system (PPMS). Next step of this paper reveals the potential use of novel hybrids of chitosan-g-glycolic acid and Pt-Fe3O4 hybrid nanoparticles in controlled drug delivery applications. The drug loaded nanohybrid scaffold is prepared by freeze drying of grafted polymer solution. Drug loading and grafting of chitosan was characterized by Fourier transform infrared spectroscopy (FTIR). The cell proliferation also shows that the prepared nanohybrids are biocompatible. The nanohybrid was found to be stable regardless of pH of the medium. Therefore, Pt-Fe3O4 hybrid nanoparticles are viable additive for sustained drug delivery and it could be applied in the field of biomedical. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Cell viability; Chitosan; drug delivery; Glycolic acid grafting; Pt-Fe3O4 hybrid nanoparticle

Heterocyclic tri-urea isocyanurate bridged groups modified periodic mesoporous organosilica synthesized for Fe(III) adsorption - Rana, Vijay Kumar; Selvaraj, M.; Parambadath, Surendran; Chu, Sang-Wook; Park, Sung Soo; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Journal of Solid State Chemistry, 2012)
To achieve a high level of heavy metal adsorption, 1,1',1 `'-(1,3,5-triazine-2,4,6-triyl)tris(3-(3-(triethoxysilyl) propyl)urea) (TTPU) was synthesized as a novel melamine precursor and incorporated on the silica surface of periodic mesoporous organosilica (PMO). The melamine modified PMOs (MPMOs) were synthesized under acidic conditions using TTPU, tetraethylorthosilicate (TEOS) and Pluronic P123 as a template and the modified PMOs were characterized using the relevant instrumental techniques. The characteristic materials were used as adsorbents for the adsorption of Fe(III) ions. Fe(III) adsorption studies revealed MPMO-7.5 to be a good absorbent with higher adsorption efficiency than other MPMOs. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Adsorption efficiency; Fe(III) adsorption; Melamine; Periodic mesoporous organosilica (PMO)

Thermal, mechanical, and rheological characterization of polypropylene/layered double hydroxide nanocomposites - Lonkar, Sunil P.; Therias, Sandrine; Leroux, Fabrice; Gardette, Jean Luc; Singh, Raj Pal (Polymer Engineering and Science, 2012)
Polypropylene (PP)/organomodified layered double hydroxide (LDH) nanocomposites were prepared in order to examine the influence of LDH content on thermal, mechanical, and rheological properties. The nanostructure examinations by X-ray diffraction (XRD) and transmission electron microscopy (TEM) confirmed the exfoliated/intercalated dispersion of LDH. Incorporation of the LDH resulted in a noteworthy improvement in the thermal stability of PP. It was shown that the addition of LDH contributed to the reinforcement effect by increasing the elastic modulus. The mechanical performance, as evaluated by stressstrain curves, reveal that PP/LDH hybrid materials showed significant contribution toward increment in elastic modulus, tensile strength but at the expense of impact strength. The rheological response showed a strong influence of LDH particles on the flow behavior of the PP/LDH melt which resulted in enhancement of storage, loss of moduli, and complex viscosity of nanocomposites. Therefore, the nanocomposites have higher moduli but better processibility compared with pure PP. Overall, the results indicated that the LDH particles in nanometer size might act as potential reinforcing agent for polypropylene. POLYM. ENG. SCI., 52:20062014, 2012. (c) 2012 Society of Plastics Engineers

Glycolic acid functionalized chitosan-Au-Fe3O4 hybrid nanoparticle based nanohybrid scaffold for drug delivery - Kumari, Sangeeta; Singh, Raj Pal (International Journal of Biological Macromolecules, 2013)
The research on biomedical applications of nanoparticles has seen an upsurge in recent years due to their unique capabilities in treatment of ailments. The present paper reports the synthesis of Au-Fe3O4 hybrid nanoparticles. The formation of these nanoparticles was confirmed by transmission electron microscopy (TEM) and physical property measurement system (PPMS). Next step of this paper reveals potential use of novel hybrid of chitosan-g-glycolic acid and Au-Fe3O4 hybrid nanoparticles in controlled drug delivery and tissue engineering applications. Grafting of glycolic acid and drug loading in porous scaffold was characterized by Fourier transform infrared spectroscopy. The nanohybrid scaffolds were found to be stable regardless of pH of the medium and play a key role in cell adhesion, proliferation and migration. Au-Fe3O4 hybrid nanoparticles reinforcement was found to control the drug (cyclophosphamide) release rate in phosphate buffer saline solution (pH 7.4). Therefore, Au-Fe3O4 hybrid nanoparticles are viable additive for formulating sustained drug delivery systems based on glycolic acid grafted chitosan. The cell proliferation profile also shows that prepared nanohybrid is biocompatible providing suitable substrates for tissue engineering. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Au-Fe3O4 hybrid nanoparticles; Chitosan Glycolic acid grafting; Drug delivery system; Physical property measurement system

Glycolic acid-functionalized chitosan-Co3O4-Fe3O4 hybrid magnetic nanoparticles-based nanohybrid scaffolds for drug-delivery and tissue engineering - Kumari, Sangeeta; Singh, Raj Pal (Journal of Materials Science, 2013)
In the present work, Co3O4 was prepared by hydrothermal process, which is further used for the synthesis of Co3O4-Fe3O4 hybrid nanoparticles. The formation of Co3O4-Fe3O4 nanoparticles was investigated by transmission electron microscopy and physical property measurement system. In the next step, the drug-loaded novel nanohybrid porous scaffold based on chitosan-g-glycolic acid and Co3O4-Fe3O4 nanoparticle was prepared by freeze drying technique. The grafting of glycolic acid on chitosan drug loading in porous scaffold was characterized by Fourier transform infrared spectroscopy. The nanohybrid scaffolds were found to be stable regardless of the pH of the medium and play an important role in cell adhesion, proliferation, and migration. Co3O4-Fe3O4 hybrid nanoparticles' reinforcement was found to control the drug (cyclophosphamide) release rate in phosphate buffer saline solution (pH 7.4). Therefore, Co3O4-Fe3O4 hybrid nanoparticles are viable additives for formulating sustained drug delivery systems and could be applied in the field of biomaterials.

Chitosan and chitosan-co-poly(epsilon-caprolactone) grafted multiwalled carbon nanotube transducers for vapor sensing - Rana, Vijay Kumar; Akhtar, Shamim; Chatterjee, Sudipta; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Journal of Nanoscience and Nanotechnology, 2014)
Vapor sensitive transducer films consisting of chitosan grafted (CNT-CS) and chitosan-co-polycaprolactone grafted (CNT-CS-PCL) multiwalled carbon nanotubes were prepared using a spray layer-by-layer technique. The synthesized materials (CNT-CS and CNT-CS-PCL) were characterized by Fourier transform infrared spectroscopy, C-13 CP/MAS solid state nuclear magnetic resonance spectroscopy and thermogravimetric analysis. Both CNT-CS and CNT-CS-PCL transducers were analyzed for the response of volatile organic compounds and toluene vapors. The ranking of the relative resistance (A(r)) for both chitosan based transducers were as follows: toluene < chloroform < ethanol < methanol. The CNT transducer (CNT-CS) was correlated selectively with an exponential law to the inverse of Flory-Huggins interaction parameters, chi(12). Dosing the films on the interdigitated electrodes with methanol, ethanol, chloroform and toluene vapors increased the film resistance of CNT-CS but decreased the resistance of CNT-CS-PCL compared to that of the reported transducers.
Keywords: Biocompatibility; Chitosan; MWCNTs; Poly(epsilon-caprolactone); Vapour Sensing

Stabilization of γ-sterilized low-density polyethylene by synergistic mixtures of food-contact approval stabilizers - Alariqi, Sameh A. S.; Al-Areqi, Niyazi A. S.; Alaghbari, Elyas Sadeq; Singh, Raj Pal (International Journal of Industrial Chemistry, 2017)
In our previous studies, we have found the synergistic combinations of stabilizers which follow different mechanisms of stabilization and are approved for food contact applications. The present attempt is to test the potentials of those systems in stabilizing γ-sterilized low-density polyethylene (LDPE). The results were discussed by comparing the stabilizing efficiency of mixtures with and without phenol systems as well as with their counterparts of isotactic polypropylene (iPP) and ethylene-propylene copolymers (EP) matrices. LDPE has been melt-mixed with tertiary hindered amine stabilizer (tert-HAS), oligomeric HAS stabilizer, phenolic and organo-phosphite antioxidants and subjected to γ-sterilization. Stabilization in terms of changes in oxidation products, tensile properties, yellowing and surface morphology was evaluated by FT-IR spectroscopy, Instron, colorimetry, and scanning electron microscopy (SEM), respectively. The results of the present study confirm the validity of those systems for protecting various polyolefins against γ-sterilization. The results showed that the synergism, antagonism and the trend in stabilization efficiency of the binary, ternary and quaternary stabilizer systems were almost similar in LDPE, iPP and EP matrices. The binary system of oligomeric HAS and tert-HAS has shown the antagonistic effect of stabilization, whereas their combination with organo-phosphite has exhibited synergistic effect even at higher doses of γ-sterilization. The combination of oligomeric HAS, tert-HAS, organo-phosphite and hindered phenol exhibited improved stabilization efficiency than single or binary additive systems. The phenol systems have shown long term of stability than that of phenol-free systems. It was found that the consumption of oligomeric stabilizer significantly depends on the components of stabilization mixture. It was concluded that the stability of polyolefins (LDPE, iPP and EP) against γ-sterilization can be achieved by blends of different stabilizers which are approved for food contact applications.

Chitosan-based bionanocomposites for biomedical application - Kumari, Sangeeta; Singh, Raj Pal; Chavan, Nayaku N.; Annamalai, Pratheep K. (Bioinspired Biomimetic and Nanobiomaterials, 2018)
Natural polymers have greatly impacted the advancement of modern medicine. Natural polymer-based biomaterials are biodegradable. A significant advantage of natural polymers is that they can be broken down and removed from the body after they have served their function. A wide range of novel biomaterials from natural polymers has been investigated to meet new challenges in medical science. Chitosan is one of the natural polymers which have been widely used in the biomedical field. Nanotechnology is one of the most popular areas of current research. In the area of nanotechnology, polymer and metal/metal oxide nanoparticle matrix-based nanocomposites have generated a significant amount of attention in the recent literature. These bionanocomposites have wide-ranging applications in drug delivery and tissue engineering. This paper discusses polymer-metal/metal oxide nanoparticle matrix-based nanocomposite biomaterials and their applications in the biomedical field - that is, drug delivery and tissue engineering applications.

Characterization of a novel nanocomposite film based on functionalized chitosan-Pt-Fe3O4 hybrid nanoparticles - Kumari, Sangeeta; Singh, Raj Pal; Chavan, Nayaku N.; Sahi, Shivendra V.; Sharma, Nilesh (Nanomaterials, 2021)
The development of organic-inorganic hybrids or nanocomposite films is increasingly becoming attractive in light of their emerging applications. This research focuses on the formation of a unique nanocomposite film with enhanced elasticity suitable for many biomedical applications. The physical property measurement system and transmission electron microscopy were used to analyze Pt-Fe3O4 hybrid nanoparticles. These nanohybrids exhibited magnetic effects. They were further exploited to prepare the nanocomposite films in conjunction with a chitosan-g-glycolic acid organic fraction. The nanocomposite films were then examined using standard techniques: thermogravimetric analysis, X-ray diffraction, Fourier transform infrared spectroscopy, and atomic force microscopy. Tensile strength testing demonstrated a significantly greater elastic strength of these nanocomposite films than pure chitosan films. The water absorption behavior of the nanocomposites was evaluated by measuring swelling degree. These nanocomposites were observed to have substantially improved physical properties. Such novel nanocomposites can be extended to various biomedical applications, which include drug delivery and tissue engineering.
Keywords: Chitosan; nanocomposite films; Pt-Fe3O4 hybrid nanoparticles; tensile strength testing; Thermogravimetric analysis